Initial clinical presentation of cervical cancer patients at the Pietersburg Hospital, Limpopo Province, South Africa - Mohuba, Maite Edna (My University, 2015)
Cervical cancer is a serious public health problem in both developed and developing countries. It is said to be the leading cause of death for women from developing countries as compared to other types of cancers. The aim of the study was to determine the initial clinical presentation of cervical cancer patients at the Pietersburg Hospital, Limpopo Province in South Africa. The objectives were to establish the demographic profile of cervical cancer patients, to identify the stage at initial clinical presentation, and to describe the factors that led to initial clinical presentation of cervical cancer patients at the Pietersburg Hospital in Limpopo Province, South Africa.The researcher conducted a quantitative retrospective cross-sectional survey by examining the records of cervical cancer patients seen for a period of three years from January 2012 to December 2014 at the Pietersburg. The results indicated that most patients, particularly the elderly, presented for the first time at the hospital with advanced stages of cervical cancer. Factors, such as age and place of residence contributed to this late presentation. There is a need for improved data capturing of information about marital status and parity to further assess the influence these two elements might have on the clinical presentation of cervical cancer. Furthermore, availability and facilities for screening should be improved because early detection of cervical cancer prevents progression to advanced stage of the disease. More awareness campaigns about risk factors of cervical cancer have to be implemented and a study is needed to establish why most patients with advanced stage cervical cancer are from Sekhukhune and Vhembe Districts, particularly the former Venda and Gazankulu Regions.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Cervical cancer; Screening; Cervical cancer; Pharmacology